1295 CAN THE HOSPITAL FRAILTY RISK SCORE BE USED TO PREDICT POST-OPERATIVE OUTCOMES IN SPINAL SURGERY?. (16th January 2023) - Johnston, A; Rose, B; Bilmen, J; Fale, A
Abstract: Introduction: Frailty is a syndrome associated with increasing numbers of elderly hospital admissions and prolonged inpatient stays (Archibald et al, Geriatrics, 2020, 20, 17) . In 2015, an estimated 14% of inpatients in the UK were considered to have a degree of frailty, representing an approximate annual cost to the NHS of £5.8 billion (Soong et al, BMJ Open, 2015, 5, e008456; Han et al, Age and Aging, 2019, 48, 665-671) . Frailty is poorly defined; there are discrepancies in existing literature on how to best quantify frailty. It is recognised there is a higher risk of adverse outcomes in this vulnerable population due to lack of physiological reserve (Clegg et al, The Lancet, 2013, 381, 752-762) . The Hospital Frailty Risk Score (HFRS) is a recent development to measure frailty and identify patients at risk (Gilbert et al, The Lancet, 2018, 391, 1775-1782) . This study sought to establish whether the HFRS could be used in patients with degenerative spinal disease, undergoing decompression surgery, to predict post-operative outcomes. Methods: A retrospective service evaluation of eligible patients in Leeds Teaching Hospitals Trust between March 2018 - March 2020. The exposure was the patients' HFRS; the outcome was the length of stay (LOS) until physiotherapy discharge. Data was sourced from electronic records. Results: 214 patients were identified with an available HFRS value. Patients were categorised as low, intermediate or high frailty. Kruskal-Wallis test for LOS and categorical HFRS: X2 =8.673, p<0.05. The median HFRS value was 1.25 (interquartile range 0.00 to 3.35). Mann-Whitney U test for LOS and numerical HFRS: W=29297, p<0.05. Conclusions: The results of this study complement pre-existing studies of similar natures, evaluating frailty scoring and post-operative outcomes, thus, supporting the potential for standardised use of HFRS alongside holistic patient examination to streamline pre-assessment, improve outcomes and reduce the NHS frailty burden.